Chaotic spreading of epidemics in complex networks of excitable units - F. S. Vannucchi; S. Boccaletti (Mathematical Biosciences and Engineering)
We explore the dynamics of an epidemiological disease spreadingwithin a complex network of individuals. The local behavior of the epidemics ismodelled by means of an excitable dynamics, and the individuals are connectedin the network through a weighted small-world wiring. The global behavior ofthe epidemics can have stationary as well as chaotic states, depending uponthe probability of substituting short-range with long-range interactions. Wedescribe the bifurcation scenario leading to such latter states, and discuss therelevance of the observed chaotic dynamics for the description of the spreadingmechanisms of epidemics inside complex networks.